Guiding schools on their journey towards inclusion. Issue 1 (2nd January 2020) - Azorín, Cecilia; Ainscow, Mel
ABSTRACT: Inclusion is increasingly recognised as a major driving force for educational reform and is a central goal of the international political agenda. This paper describes and analyzes how a group of schools in one region of Spain trialled a newly developed review instrument, named 'Themis', with the aim of guiding their efforts to promote greater inclusion. In so doing, the paper focuses on how schools can be helped to review progress on their journey to becoming more inclusive. Some of the challenges perceived in its use were the practicalities of generating credible evidence and the problem of making sense of this evidence; the need to develop trust among stakeholders; and the relevance of resolving contradictions and tensions, and deciding on priorities for moving forward. A strong theme that permeates the analysis presented in the paper is the importance of developing review instruments that relate to particular contexts and take account of the varied ideas of those involved.